International Environmental Law and Policy for the 21st Century : 2nd Revised Edition. - Nanda, Ved (International Environmental Law., 2012)
A significant contribution to the field, and a welcome addition to the growing literature on international environmental law and an important reference for every scholar, lawyer, and layperson interested in the field.